Electrochemical plating of Sn – Ag alloy applicable as a solder - Vrublevskaya, Olga N.; Shikun, Marina A.; Vorobyova, Tatiana N.; Rabenok, Anna M.; Gunich, Angelina S.; Melnikova, Svetlana G. (Journal of the Belarusian State University. Chemistry, 2018)
The additions of hydroquinone, 1,4-butandiol and citrate ions to the known strongly acidic sulfate-thiourea solution for electrochemical deposition of Sn – Ag low-melting alloy are proposed, which provide to obtain the alloys of composition near to the eutectic one. It is shown that varying the content of the additions and current density it is possible to control tin content in the alloy in the range of 73–96 wt. %, the rate of coatings deposition from 2.7 to 15.6 µm/h, the total current yield in the range of 55–99 %. It is determined that coatings consist of fine silver grains less than 0.5 µm in size and lamellar tin crystals 3–20 µm in size, increasing with the rise of tin fraction in the alloy. According to thermal analysis data the maximum of endothermic peak in DSC curves corresponding to the melting of Sn – Ag alloy with tin content over 73 wt. % is found at 223.5 °С, that is close to the melting temperature of the eutectic. The area of this peak increases with tin quota in the alloy. Sn – Ag coatings containing more than 93 wt. % of tin, similar in composition to the eutectic are characterized by high spreading of the molten solder even better as compared with tin, which makes these coatings promising for soldering.